Development Strategy for Precision Manufacturing of Composite Components Facing 2035 - Shan Zhongde; SongWenzhe; Fan Congze; Wang Jun (中国工程科学, 2023)
Advanced composite materials exhibit advantages of high specific strength, high specific modulus, and excellent designability. They are widely used in aerospace, rail transit, and other fields, and are strategic resources for industrially developed countries. Ensuring and improving the supply capacity of advanced composite materials and making breakthroughs in the design and forming, processing and assembling, testing and repairing technologies of large and complex composite components are of strategic significance in strengthening China’s manufacturing sector. In this study, the current status and trends of precision manufacturing of composite components are analyzed, and the key technologies and equipment for precision manufacturing of composite components, including high-precision numerical control winding, automatic placement, preform forming, additive manufacturing, and high-performance carbon fiber production, are summarized. After specifying the key problems limiting the development of composite manufacturing technologies, we propose the development goals by 2035. Accordingly, suggestions are proposed including establishing national innovation institutions, planning major science and technology projects, enhancing disciplines development and talent fostering, strengthening international communication and collaboration, and focusing on significant scientific innovation and technological breakthroughs, thus to provide high-quality scientific and technological support for national major projects and important model projects.